Development of a Vocational Career Guidance Module to Improve Career Decision-Making Skills of Social Work Students - Latifah, Laila; Basyirun, Basyirun; Ihsani, Ade Novi Nurul; Supraptono, Eko (Journal of Vocational and Career Education, 2026)
Career decision-making challenges remain a critical issue in vocational education, particularly at the secondary level, where many students choose majors that do not align with their interests and abilities. This condition highlights the need for early career guidance to help students map their career paths and develop their competencies appropriately. This study aims to develop a vocational career guidance module for Social Work students; to determine the validity of the module based on expert evaluation; to analyze the validity and reliability of the test instruments; and to examine the effectiveness, efficiency, practicality, and implementability of the module. This research employed the ADDIE R&D model involving 60 tenth-grade students of SMK Negeri 5 Samarinda, divided into experimental and control groups. The results indicate that the module is highly feasible, with material expert validation at 94% and media expert validation at 91%. The test instrument demonstrates strong quality, with 30 of 33 items deemed valid and a Cronbach’s Alpha reliability of 0.925. The module is proven to be highly effective (91.6%), efficient (89.6%), and practical (93.8%), with an implementation rate of 86%. In addition, teacher and student responses reached 90.8% (excellent category). Statistical analysis confirms significant improvement in students’ career decision-making skills, with tcount = 13.396 > ttable = 2.002, Sig. = 0.000, and an N-gain score of 0.72964 (high category). These results show that the developed module effectively enhances the career decision-making skills of Social Work vocational students.